A call to the Church: Embrace children with disabilities - Natalie Ann Flickner (Health for All Nations, 2015)
Children with Disabilities are one of the groups of children most in need globally. The author uses her personal story of growing up as a child with mild cerebral palsy to express her solidarity and highlight the multiple needs of children with disabilities around the world. These children should no longer be stigmatized by the world wide church but instead be embraced and ministered to in the name of Jesus.